Sustainable development, international aviation, and treaty implementation - De Mestral, Armand 1941-; Fitzgerald, P. Paul ca. 20./21. Jh; Ahmad, Tanveer ca. 20./21. Jh (Treaty implementation for sustainable development, 2018)
In 1944 the Chicago Convention set out the foundations of public international law regulating international air transport, but until 2016 no international agreement existed to limit its environmental impact. Sustainable Development, International Aviation, and Treaty Implementation explains why the CORSIA scheme adopted by the International Civil Aviation Organization in 2016, should be implemented in 2020 even though the adequacy of this scheme is still open to doubt and criticism. This book seeks to examine the many dimensions of the effort to contain greenhouse gas emissions from aircraft in a manner consonant with the principles of sustainable development, and examines the development of international law and policy in an area that has remained largely outside the general framework of international environmental law. International civil aviation is a significant polluter of the atmosphere, and in this volume, a group of air law and sustainable development law specialists considers how the international community can respond